노인유사 체험이 노인요양시설 종사자의 노인돌봄태도, 노인에 대한 이해도, 업무만족도 및 직무수행에 미치는 영향 - 정혜영(Hye Young Joung); 현혜진(Hye Jin Hyun) (지역사회간호학회지, 2012)
Purpose: This research is to understand the effects of senior simulation on employees of elderly care facilities and utilize it in their job training. Methods: This research is a nonequivalence control group pre-to-post quasiexperiment research. 18 employees who have experienced senior simulation are set as test group and 18 other employees who have not experienced senior simulation are set as control group. Results: The hypothesis that 'the test group which has experienced senior simulation will show a positive change in their attitude on elderly care, compared to the control group' and 'the test group which has experienced senior simulation will show a positive change in understanding of elders, compared to the control group' was supported. The hypothesis that 'the test group which has experienced senior simulation will show a positive change in job satisfaction and performance of duties, compared to the control group' was dismissed. Conclusion: The senior simulation seems to contribute to elderly care facilities employees' change in their viewpoints of elders and broaden their understanding of them. The senior simulation was meaningful to provide basic help with implementing job training programs.